Football Fans’ Emotions: Uncertainty Against Brand Perception - Shakina, Elena; Gasparetto, Thadeu; Barajas, Angel (Frontiers in Psychology, 2020)
Football is an industry driven by emotions. Fans experience many different emotions related to their teams. This paper aims to inspect how emotions impact attendance at football matches examining whether football fans prefer to watch high competitive matches or matches of good teams with star-players. The paper also considers behavioral and emotional differences of match spectators when brand-team plays away or at home. Importantly, that we are also looking for the effects that the expectations of these emotions are embedded in the tickets’ price mechanism. We use data from three seasons of Brazilian State championship with information about more than 1100 matches. OLS estimator with the moderation marginal effects allows analysis of brand-team playing jointly with different level of the uncertainty of outcomes measured by relative level of divisions of rivals. We look for the difference between the marginal contribution of brand-team and uncertainty of outcomes that might change under some conditions. The analysis is performed later using two subsamples and finally we address the problem of endogeneity in price using instrumental variable. From our results, the main findings are: first, that price for tickets does not affect much the demand when a brand-team is playing. In case of competitive matches between non-brand-teams, price behavior is according to the rationality of the demand curve having negative impact. The fact that price is not relevant for matches with brand-team comes to corroborate the idea that fans are driven more by emotions than for economic reasoning. Second, the phenomena of highly competitive matches do not work when a brand-team is playing against a small one. Third, the effect of a brand-team playing is relatively more important than the uncertainty of outcome. The last two findings mean that the satisfaction of watching star-players or big-teams is stronger than the emotion brought by a competitive match.